Carbon Monoxide Activation by a Molecular Aluminium Imide: C−O Bond Cleavage and C−C Bond Formation. Issue 12 (18th February 2020) - Heilmann, Andreas; Hicks, Jamie; Vasko, Petra; Goicoechea, Jose M.; Aldridge, Simon
Abstract: Anionic molecular imide complexes of aluminium are accessible via a rational synthetic approach involving the reactions of organo azides with a potassium aluminyl reagent. In the case of K2 [(NON )Al(NDipp)]2 (NON =4, 5‐bis(2, 6‐di iso propylanilido)‐2, 7‐di‐tert‐butyl‐9, 9‐dimethyl‐xanthene; Dipp=2, 6‐di iso propylphenyl) structural characterization by X‐ray crystallography reveals a short Al−N distance, which is thought primarily to be due to the low coordinate nature of the nitrogen centre. The Al−N unit is highly polar, and capable of the activation of relatively inert chemical bonds, such as those found in dihydrogen and carbon monoxide. In the case of CO, uptake of two molecules of the substrate leads to C−C coupling and C≡O bond cleavage. Thermodynamically, this is driven, at least in part, by Al−O bond formation. Mechanistically, a combination of quantum chemical and experimental observations suggests that the reaction proceeds via exchange of the NR and O substituents through intermediates featuring an aluminium‐bound isocyanate fragment. Abstract : C−C coupling : An isolable molecular aluminium imide with a highly polarized Al−N bond has been found to react with CO via C≡O bond cleavage and C−C coupling. Key proposed intermediates in this transformation feature an aluminium‐bound isocyanate fragment.